A novel detailed analytical approach for determining the optimal design of FRP pressure vessels subjected to hydrostatic loading: Analytical model with experimental validation. (15th February 2020) - Hajmohammad, Mohammad Hadi; Tabatabaeian, Ali; Ghasemi, Ahmad Reza; Taheri-Behrooz, Fathollah
Abstract: A new practical analytical approach has been developed in order to reach the optimal fiber orientation in design of fiber reinforced polymer pressure vessels (FRPPVs) subjected to hydrostatic pressure. The method consists of analytical solutions along with optimizing process in which different decisive factors such as buckling pressure, weight, failure of fiber and matrix, thickness, number and angle of layers are considered as problem constraints. In analytical part, besides the buckling analysis, Tsai-Wu and Hashin failure criteria are employed to analyze the failure of the structure. Then, the genetic algorithm (GA), as a robust optimization method, is applied to achieve the optimal orientation pattern with minimum weight and maximum buckling load. In addition, the impact of mapped fitness function in optimization process is exclusively analyzed. Next, to validate the reliability and effectiveness of the proposed approach, two different experimental methods, including the strain gauge and volume control methods, are performed and measured buckling pressure is compared with the analytical results. The results indicated that using the proposed approach, critical buckling load increases by 40% while the weight is reduced by 15%, simultaneously.